Toward the Humilocene: The Embodied Rhetoric of St. Francis of Assisi - Rosenfeld, Cynthia (The Trumpeter, 2021)
In support of abandoning the term Anthropocene in favor of calling our current epoch the Humilocene, this essay addresses Lynn White, Jr.’s critique that a particular understanding of Christian creation theory is the cause of our current ecological crisis, briefly discussing contemporary attempts to read the Old and New Testaments in a manner harmonious with White’s critiques and recommendations, and explores the embodied rhetoric of St. Francis of Assisi. I argue that Francis’s manner of embodying three of Cicero’s canons of rhetoric is relevant to contemporary rhetoricians and to deep ecologists. Francis’s rhetorical style is an embodied rhetoric that assists advocacy by transforming everyday experiences, builds community through an embrace of agapē, and, through Francis’s adoption of the position of “servant,” helps establish a more equal distribution of power. Franciscan rhetoric offers equipment for moving through the humiliation, humility, and redemption of the Humilocene.